Nothing like sunshine : a story in the aftermath of the MLK assassination - Kamin, Ben (Michigan State University Press, 2010)
Rabbi Ben Kamin has written a definitive personal expression about race, coming of age in the 1960s, a forbidden friendship, and his personal love for Dr. Martin Luther King Jr. This is a story that spans a four-decade search for a lost high school chum, a deep misunderstanding, and a coming to terms with an America painfully evolving from the blood of MLK to the promise of Barack Obama. The book is a remembrance of Kamin's life at Cincinnati's notorious Woodward High School, a microcosm of the 1960s and of America itself, as well as detailing Kamin's search-for Clifton, for America, for the key to understanding what race relations really are in the United States. Simultaneously, it is the story of the emerging rabbi's search for the legacy of his spiritual mentor, Dr. Martin Luther King Jr., taking Kamin from Cincinnati to Cleveland to Memphis to New Orleans and other points, and constantly bringing him home to his friend Clifton and "the heaving hallways" of that high school